OTIMIZAÇÃO DA EXTRAÇÃO DE COMPOSTOS BIOATIVOS DAS FOLHAS DE Campomanesia sessiliflora (O. BERG) MATTOS. - LOUREIRO, Raquel Parra; CASTRO, Thiago Luis Aguayo; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2025)
.